2010
DOI: 10.1111/j.1538-7836.2010.04015.x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent miscarriage and antiphospholipid antibodies: prognosis of subsequent pregnancy

Abstract: Summary. Background: Although women with antiphospholipid antibodies (APLAs) are at increased risk of recurrent miscarriage, the outcome of a subsequent pregnancy is not clearly elucidated. Objectives: To assess the pregnancy outcome of a subsequent pregnancy in women with APLAs and compare this outcome with women with unexplained recurrent miscarriage. Methods: We performed a cohort study among all women who attended the Miscarriage Clinic at Liverpool WomenÕs Hospital between 1987 and 2006 after being referr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 47 publications
(70 reference statements)
0
49
0
1
Order By: Relevance
“…Some authors quote the age of fetal viability or a gestational age of 24 weeks or less in defining recurrent miscarriage [5], others regard recurrent miscarriage as the loss of 2 or more consecutive pregnancies [11,12]. In this review, RSM is defined as the loss of 3 or more consecutive pregnancies before 20 weeks' gestation, a definition that has been widely adopted [1,2,3,4,6,7,10,13,14]. It is pertinent to state here that in our practice in Kuwait, we do commence RSM investigations in patients 35 years and older who have had 2 or more previous consecutive miscarriages because of the decline in fertility with increasing maternal age.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors quote the age of fetal viability or a gestational age of 24 weeks or less in defining recurrent miscarriage [5], others regard recurrent miscarriage as the loss of 2 or more consecutive pregnancies [11,12]. In this review, RSM is defined as the loss of 3 or more consecutive pregnancies before 20 weeks' gestation, a definition that has been widely adopted [1,2,3,4,6,7,10,13,14]. It is pertinent to state here that in our practice in Kuwait, we do commence RSM investigations in patients 35 years and older who have had 2 or more previous consecutive miscarriages because of the decline in fertility with increasing maternal age.…”
Section: Introductionmentioning
confidence: 99%
“…In Cohn et al 's study (N = 693), only 176 women (25%) were aPL-positive, while the rest had unexplained RPL. 45 Of the aPL-positive women, 69% (n = 122) had a subsequent live birth compared with 63% (n = 324) of the women with unexplained RPL (odds ratio [OR] = 1.3; 95% CI: 0.9-1.9). When the authors analysed the results, they found that 79% of aPL-positive women receiving a combination of heparin and LDA had a live birth compared with 62% of those receiving LDA alone (adjusted OR = 2.7; 95% CI: 1.3-5.8).…”
Section: Treatment Of Women With Antiphospholipid Syndrome and Recurrmentioning
confidence: 99%
“…This prothrombotic condition protects against severe hemorrhage during delivery but it may also increase the risk of thrombosis, especially during the first 3 months after delivery. When acquired and/or inherited thrombophilia risk factors are present, they can result in a further imbalance of the prothrombotic process that may increase the risk of thromboembolism, both for venous thromboembolic disease and for adverse pregnancy outcomes [3,4,5]. Pregnancy loss is a relevant public health issue and, despite extensive investigations, a significant proportion of cases remain unexplained [6].…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy loss is a relevant public health issue and, despite extensive investigations, a significant proportion of cases remain unexplained [6]. The role of acquired thrombophilia antiphospholipid syndrome as a common and potentially treatable cause of recurrent pregnancy loss is well established [3,4]. Conversely, the role of inherited thrombophilia, reported in many published papers and analyzed in several meta-analyses, is currently not well established [5,7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%